Impact of esophagogastroduodenoscopy and ileocolonoscopy on diagnosis and therapy in patients with rheumatic diseases—a retrospective cohort study. Issue 4 (3rd July 2016) - Schäfer, Valentin Sebastian; Fleck, Martin; Ehrenstein, Boris; Peters, Ann-Kathrin; Hartung, Wolfgang
Abstract: Objectives : Many rheumatic diseases as well as their medications may cause gastrointestinal (GI) pathologies; in addition, some primary GI diseases may contribute or lead to rheumatic disease manifestations. The aim of this study is to analyze the clinical relevance of esophagogastroduodenoscopy (EGD) and ileocolonoscopy (IC) in patients suffering from inflammatory rheumatic diseases. Methods : A retrospective chart review was performed for all rheumatological inpatients who underwent EGD and/or IC within 2 years. Results : Within 2 years, 456 patients (261 female, 195 male) underwent 752 endoscopic investigations of the GI tract (419 EGDs and 333 ICs). Of all patients, 152 (33.3%) did not report any GI complaints. However, 28 of these asymptomatic patients (18.4%) suffered from esophagitis, a gastric ulcer could be identified in 20 patients (13%), whereas unspecific colitis was diagnosed in 19 patients (12.5%). In addition, 14 patients (9.2%) suffered from clinically unapparent Crohn's disease and two patients from Whipple's disease. In one patient with polymyalgia rheumatica, colon cancer was diagnosed. Altogether 304 patients reported GI complaints. Of these, 292 (39%) endoscopic investigations had impact on the final diagnosis or therapeutic strategy. The antirheumatic medication or the concomitant medication was changed in 18% of the patients due to the endoscopic findings; in 29 patients (6.5%) the initially clinically presumed diagnosis had to be corrected. In 70 patients (15%) with an undefined rheumatic diagnosis prior to endoscopy, endoscopic findings were decisive to establish the final diagnosis. Conclusion : EGD and IC have a high diagnostic impact on patients with rheumatic diseases presenting with or without concomitant GI symptoms.